E-cigarettes: promise or threat? - Nachiappan, Arun C.; Selvavinayagam, T. S. (International Journal Of Community Medicine And Public Health, 2017)
Use of the electronic cigarette or electronic nicotine delivery system (ENDS) is increasing globally. Its vapour delivers nicotine without the 6000 odd chemicals released during cigarette smoking and the associated harm. Experts are divided on whether ENDS promise reduction in tobacco use or threaten tobacco control. This review presents up-to-date evidence. Two trials showed an increase in cessation, but not a reduction in cigarette use. Eight cohort studies showed no increase in cessation, and two cohort studies and a recent trial showed an increased reduction in cigarette use. A US population study showed association between ENDS use and smoking cessation. Nicotine addiction and potential harm to non-smokers who use ENDS are key concerns. Nicotine affects lung and brain development. An increase in accidental poisoning, though mild, is reported in children. No significant short term health effects are reported. When heated, ENDS may emit potential toxic and carcinogenic substances such as aldehydes, acrolein, flavouring agents etc. at very low levels - but their long term impact is not known. ENDS bring potential benefits to smokers, but there are concerns about their potential for nicotine addiction, gateway effect and renormalisation of smoking. However, in the UK and the US, a rise in ENDS use is associated with a fall in the prevalence of smoking. Countries differ in their approach to ENDS. India seems to be edging towards a total ban. India should collect local data and conduct research to monitor the impact and make informed, evidence based decisions, where needed.